Soil Erosion Assessment of The Post-Coal Mining Site in Kutai Kartanagera District, East Kalimantan Province - Zulkarnain Zulkarnain (International Journal of Science and Engineering, 2014)
Besides of its positive economic impact, mining activity has negative impacts to the sustainability of community development and livelihoods as mining reclamation can’t restore the land condition to its original state. The objective of this study was to determine the main factor that caused soil erosion induced in post-coal mining and defined reclamation activity that caused soil erosion. The observed parameters were site reclamation age of each companies, soil physical properties (density, texture, permeability, organic material and soil structure), rainfall rate, soil chemical properties, land cover and age of re-vegetation, plant cover. Analysis was carried out to determine the magnitude of erosion at each site unit, tolerable erosion and potential erosion level. Adequate reclamation action with good vegetative cover could be seen from erosion magnitude at five year reclamation age i.e. 1.7 ton/ha/ year- which lower than tolerable erosion i.e. 5.4 ton/ha/year. While inadequate reclamation action could be seen from erosion magnitude at nine year age of reclamation i.e. 201.1 ton/ha/year1 which higher than tolerable erosion i.e. 15.1 ton/ha/ year1. The erosion magnitude at the four month of reclamation age was 4.966,3 ton/ha with tolerable erosion was 5.3 ton/ha. The erosion magnitude that occurs in post-mining site was due to soil compaction that lowering soil permeability rate leading to slow growing of cover crop. This condition made the soil wasn’t covered from raindrop and water run-off.  In order to improve the soil condition of post-mining site into productive land, legume cover crop was recommended to be planted.